2013
DOI: 10.1038/bmt.2013.143
|View full text |Cite
|
Sign up to set email alerts
|

Effective prevention of GVHD using in vivo T-cell depletion with anti-lymphocyte globulin in HLA-identical or -mismatched sibling peripheral blood stem cell transplantation

Abstract: To investigate the impact of anti-lymphocyte globulin (ATG-Fresenius) as part of the HLA-sibling transplantation, we evaluated 238 patients (median age 48 years) with different diagnoses (AML, ALL, CML and lymphoproliferative disorders). A total of 79 patients received ATG and 159 patients did not. In the ATG group, there were more HLA-mismatched donors (6% vs 1%, p ¼ 0.02), bad risk patients (70% vs 55%, P ¼ 0.04), reduced intensity conditioning (RIC) regimens (65% vs 34%, P ¼ o0.001) and older patients (medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
6
23
1
Order By: Relevance
“…However, with the exception of one study with matched-related HSCT only, 21 these studies did not reach statistical significance. [7][8][9][10]13,22 The survival benefit shown here may be due to an improved selection of patients receiving ATG. Although the imbalance of known risk factors was adjusted for by statistical analysis, larger series of patients need to be analyzed for confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the exception of one study with matched-related HSCT only, 21 these studies did not reach statistical significance. [7][8][9][10]13,22 The survival benefit shown here may be due to an improved selection of patients receiving ATG. Although the imbalance of known risk factors was adjusted for by statistical analysis, larger series of patients need to be analyzed for confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect had already been reported in previous studies. 5,7,9,10,22,23 Incidence of CMV and EBV reactivations, as well as symptomatic viral infections and bacterial BSI, but not invasive fungal infections were increased especially when using higher dose ATG. This can be attributed to the immunosuppressive effect of ATG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of phase II studies have assessed the impact of rabbit ATG in patients given unmodified grafts after myeloablative conditioning [46][47][48][49][50][51][52] (Table 2). Collectively, these studies suggested that ATG decreased the incidence of grade III-IV acute and chronic GVHD without increasing non-relapse mortality (some studies even found lower non-relapse mortality with ATG), increased the incidence of post-transplantation lymphoproliferative disorders, and improved quality of life.…”
Section: Non-randomized Studies Comparing Anti-thymocyte Globulin Vermentioning
confidence: 99%
“…4,5 An alternative approach is to engineer the graft including T-cell depletion or administration of various subsets of T cells, such as regulatory T cells (Tregs). [6][7][8] Despite the knowledge of the impact of host APCs on GVHD induction, only a few preclinical studies have focused on targeting APCs to prevent GVHD induction. [9][10][11][12] Professional APCs internalize antigens, display peptides on their surface, and express costimulatory molecules that guide T-cell activation.…”
Section: Introductionmentioning
confidence: 99%